Analysis of Factors That Contribute to The Formation of Academic Hardiness of University Students - Fadhil Muhammad; Cece Rakhmat; Nandang Rusmana; Ipah Saripah (Universitas Pendidikan Mandalika (UNDIKMA), 2025)
This research aims to identify and analyze factors that contribute to academic hardiness in students with the 3C of Hardiness concept which includes aspects of commitment, control and challenge. The method used in this research is a cross-sectional survey with a quantitative approach, where data is collected using a standardized academic hardiness scale. The research sample consisted of 500 students spread across three state universities in West Sulawesi province. Data analysis was carried out using confirmatory factor analysis (CFA) to test the validity and contribution of each factor. The research results show that the control aspect is the factor that makes the biggest contribution to academic hardiness, with a standardized variance coefficient value of 0.605. Meanwhile, the social support indicator has the greatest influence, with a value of 0.854. These findings provide a basis for further research in designing guidance and counseling service models based on empirical evidence, by considering the main factors that contribute significantly to student academic hardiness. Apart from that, the results of this research can be a guide for guidance and counseling staff in designing more adaptive services, according to student needs.